Association of DNA methylation from the temporal cortex and cerebellum with AD‐related neuropathology and biochemistry. (20th December 2022) - Oatman, Stephanie R; Allen, Mariet; Quicksall, Zachary; Reddy, Joseph S.; Carrasquillo, Minerva M.; Wang, Xue; Liu, Chia‐Chen; Yamazaki, Yu; Nguyen, Thuy; Heckman, Michael G.; Martens, Yuka A; Zhao, Na; et al.
Abstract: Background: Alzheimer's disease (AD) is a progressive neurodegenerative disorder neuropathologically characterized by amyloid‐β (Aβ) plaques and tau neurofibrillary tangles often measured by Thal phase and Braak stage, respectively. Frequently, Aβ also deposits in the brain vasculature with severity categorized by a cerebral amyloid angiopathy (CAA) score. Assessment of these and related endophenotypes can reveal biological insights into the phenotypic variability in AD. We hypothesize that, amongst AD patients, severity of neuropathology and brain levels of AD‐related proteins are influenced by variation in DNA methylation (DNAm), the identification of which may uncover biological pathways for AD pathogenesis. To test this, we performed epigenome‐wide association studies (EWAS) using DNAm from the temporal cortex (TCX) and cerebellum (CER) with AD‐related neuropathology measures (Braak, Thal, and CAA) and brain levels of five proteins (apoE, Aβ40, Aβ42, tau, and p‐tau). Methods: DNAm from autopsy‐confirmed AD cases available through the Mayo Clinic Brain Bank was measured by reduced representation bisulfite sequencing (RRBS) from 471 brain samples, 200 of which had both TCX and CER measures. Bisulfite converted reads were sequenced on the Illumina High Seq4000 and quality filtered. Neuropathology scoring was performed by an experienced neuropathologist. TCX levels of five AD‐related proteins from three fractions (buffer‐soluble, detergent‐soluble, and insoluble) were measured by ELISA (Liu et al. 2020). Individual CpG methylation ratios were tested for association with each neuropathological and biochemical measure using the R package CpGassoc . Results: We identified multiple epigenome‐wide significant CpGs unique to each AD‐related measure. Comparisons between the TCX and CER revealed region specific CpG associations. The effects of sex, age at death, APOE genotype, and presence of genetic variants for each significant CpG association were also identified. Conclusions: Although all neuropathological and biochemical measures tested reflect core AD pathologies, our results demonstrate unique associations of epigenetic factors with these individual phenotypes, suggesting that their variability may be governed by distinct epigenetic processes. Discovery of DNAm changes that underlie specific neuropathological or biochemical outcomes can enhance our understanding of AD pathophysiology and may lead to the identification of novel gene or pathway targets for the different facets of this complex condition.